NILAI-NILAI SOSIAL DAN PENDIDIKAN ISLAM PERSPEKTIF KITAB KASYFUL GHUMMAH FI ISTHINA’IL MA’RUF WA RAHMATIL UMMAH KARYA SAYYID MUHAMMAD BIN ALAWI AL-MALIKI - Nor Mubin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
It is important for teachers to know the social values in Islamic education in order to be able to realize the goals of Islamic education, namely to make human beings who obey and submit to all Islamic teachings and prosper in the hereafter. This study uses a type of library research or literature study. The results of the final analysis, using descriptive analysis methods to present facts systematically. Based on these problems, this study intends to discuss the values ??of Islamic education, especially the values ??of social education. The author is interested in discussing this by focusing on discussing social values ??and Islamic education in the perspective of the book Kasyful Ghummah Fi Isthina'il Ma'ruf Wa Rahmatil Ummah by Sayyid Muhammad Bin Alawi Al-Maliki. In this study the results obtained are as follows: a) Social values ??in the perspective of the book Kasyful Ghummah by Sayyid Muhammd Bin Alawi Al-Maliki, contain the value of helping each other, kinship, loving each other. The values ??of Islamic Education in the perspective of the book Kasyful Ghummah by Sayyid Muhammd Bin Alawi Al-Maliki contain the meaning of the value of moral education and worship.